1983
DOI: 10.1104/pp.73.3.844
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Uptake Kinetics in Intact Soybean Plants

Abstract: The absorption characteristics of Cd2' by 10-to 12-day-old soybean plants (Glycine max cv Williams) were investigated with respect to influence of Cd concentration on adsorption to root surfaces, root absorption, transport kinetics and interaction with the nutrient cations Cu2+, Fe2 , Mn2 , and Zn2 . The fraction of nonexchangeable Cd bound to roots remained relatively constant at 20 to 25% of the absorbed fraction at solution concentration of 0.0025 to 0.5 micromolar, and increased to 45% at solution concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

17
132
3
4

Year Published

1989
1989
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 297 publications
(156 citation statements)
references
References 19 publications
17
132
3
4
Order By: Relevance
“…Cataldo et al (1983) observed inhibition of root absorption of Cd and transfer of Cd to shoots by Cu, Fe, Mn and Zn in soybean seedlings exposed to 2.5 × 10 -9 to 5 × 10 -6 M Cd. Detailed kinetic analysis suggested competitive inhibition of Cd absorption and transport by these elements, which Cataldo et al (1983) interpreted as indicating a common transport site or process for Cd, Cu, Fe, Zn and possibly Mn. The uptake of Cd by roots of perennial ryegrass exposed to 9 × 10 -8 M Cd for 3 d was depressed by the addition of Ca, Mn, and Zn (Jarvis et al 1976).…”
mentioning
confidence: 96%
See 3 more Smart Citations
“…Cataldo et al (1983) observed inhibition of root absorption of Cd and transfer of Cd to shoots by Cu, Fe, Mn and Zn in soybean seedlings exposed to 2.5 × 10 -9 to 5 × 10 -6 M Cd. Detailed kinetic analysis suggested competitive inhibition of Cd absorption and transport by these elements, which Cataldo et al (1983) interpreted as indicating a common transport site or process for Cd, Cu, Fe, Zn and possibly Mn. The uptake of Cd by roots of perennial ryegrass exposed to 9 × 10 -8 M Cd for 3 d was depressed by the addition of Ca, Mn, and Zn (Jarvis et al 1976).…”
mentioning
confidence: 96%
“…However, 8.9 × 10 -6 M Cd is a high, probably phytotoxic, level of Cd exposure, and the conclusion that Cd uptake was a passive process (Cutler and Rains 1974) should not be applied to lower, more environmentally relevant concentrations. Other authors of studies with wheat (Smeyers-Verbeke et al 1978), soybean (Cataldo et al 1983), and spruce seedlings (Godbold 1991) have concluded that there was a metabolically active component in total cadmium accumulation by intact plants. In these studies, active accumulation of Cd was observed to occur only at lower Cd concentrations (2.5 to 90 × 10 -9 M) or to be relatively more significant at lower concentrations.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, the effects of Mn starvation reducing Cd uptake and plant concentrations should be noted, indicating that this Mn-Cd interaction was not owed to true cation antagonism. Further, Cd, Cu, Fe, Zn and possibly Mn share a common transport site or process in Cd-treated soybean (Cataldo et al, 1983), tomato (Baszynski et al, 1980) and Phytolacca americana L. (a Mn-Cd hyperaccumulator) (Peng et al, 2008).…”
Section: Discussionmentioning
confidence: 99%